Stem cell factor-mediated wild-type KIT receptor activation is critical for gastrointestinal stromal tumor cell growth - Bai, Chen-Guang (World journal of gastroenterology : WJG, 2012)
AIM： To clarify the biological role of stem cell factor （SCF）-mediated wild-type KIT receptor activation in gastrointestinal stromal tumor （GIST） growth. METHODS： The co-expression of wild-type KIT receptor and SCF was evaluated in 51 GIST samples using mutation analysis and immunohistochemistry, and the results were correlated with clinicopathological param- eters, including the mitotic count, proliferative index （Ki-67 immunohistochemical staining）, mitotic index （phospho-histone H3 immunohistochemical staining） and apoptotic index （terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling）. Using primary cultured GIST cells, the effect of SCF-mediated wild-type KIT receptor activation was determined by western blotting, methyl thiazolyl tetrazolium （MTT）, and apoptosis assays. RESULTS： We found that wild-type KIT receptor and SCF protein were expressed in 100% and 76.5% of the 51 GIST samples, respectively, and the co-expression of wild-type KIT receptor and SCF was associated with known indicators of poor prognosis, including larger tumor size （P = 0.0118）, higher mitotic count （P = 0.0058）, higher proliferative index （P = 0.0012）, higher mitotic index （P = 0.0282）, lower apoptosis index （P = 0.0484）, and increased National Institutes of Health risk level （P = 0.0012）. We also found that the introduction of exogenous SCF potently increased KIT kinase activity, stimulated cell proliferation （P 〈 0.01） and inhibited apoptosis （P 〈 0.01） induced by serum starvation, while a KIT immunoblocking antibody suppressed proliferation （P = 0.01） and promoted apoptosis （P 〈 0.01） in cultured GIST cells. CONCLUSION： SCF-mediated wild-type KIT receptor activation plays an important role in GIST cell growth. The inhibition of SCF-mediated wild-type KIT receptor activation may prove to be particularly important for GIST therapy.